Understanding the Barriers to Task Sharing in Caesarean Section Delivery by Assistant Medical Officers (Tanzania Medical Journal, 2025)
BackgroundShortage of skilled human resources for health necessitated task sharing in developing countries. Demand for advanced clinical work in Tanzania necessitated training of Assistant Medical Officers (AMOs) cadre which fitted between Clinical Officer (CO) and Medical Doctors (MD) responsibilities. Practically, AMO executed responsibilities intended primarily to MDs at district health services including performance of Caesarean Section (CS). While their work is significant, scholars and practitioners raised concern on AMO performance of CS. This paper aimed to analyse barriers to implementing task sharing in CS delivery by practising AMOs and those in managerial positions.MethodsAn explorative case study design was carried out in four different zones to include one district in each of selected zones. The districts studied included Handeni, Kasulu, Kilombero, and Masasi. In-depth interview guide exploring barriers to implementing task sharing in CS was used to interview 18 AMOs in clinical and managerial roles. A Hybrid thematic approach was used to analyse collected data.  FindingsFive themes emerged illustrating barriers to task sharing in CS by AMO. These included unstructured internship programme, unorganized licensing system, shortage of equipment and medical supplies, weak supervision of AMOs together with other cadres involved in task sharing and limited benefits after graduation.ConclusionThe findings of this study underscore the fact that barriers limiting implementation of task sharing in CS delivery by AMOs may have potential to negatively influence the performance of this cadre. A comprehensive approach aiming to improve internship, professional regulation, mentorship and statutory benefits may provide conducive environment for AMOs to perform better in task sharing teams. Further, improvement in functional equipment and medical supplies in health facilities create enabling environment for AMOs to perform CS as part of task sharing.